Development of a model for baffle energy dissipation in liquid fueled rocket engines - Miller, Nathan A., author; Kirkpatrick, Allan T., advisor; Duflot, Jeanne, committee member; Williams, John D., committee member (Colorado State University. Libraries, 2010)
In this thesis the energy dissipation from a combined hub and blade baffle structure in a combustion chamber of a liquid-fueled rocket engine is modeled and computed. An analytical model of the flow stabilization due to the effect of combined radial and hub blades was developed. The rate of energy dissipation of the baffle blades was computed using a corner-flow model that included unsteady flow separation and turbulence effects. For the inviscid portion of the flow field, a solution methodology was formulated using an eigenfunction expansion and a velocity potential matching technique. Parameters such as local velocity, elemental path length, effective viscosity, and local energy dissipation rate were computed as a function of the local angle α for a representative baffle blade, and compared to results predicted by the Baer-Mitchell blade dissipation model. The sensitivity of the model to the overall engine acoustic oscillation mode, blade length, and thickness was also computed and compared to previous results. Additional studies were performed to determine the sensitivity to input parameters such as the dimensionless turbulence coefficient, the location of the potential difference in the generation of the dividing streamline, the number of baffle blades and the size of the central hub. Stability computations of a test engine indicated that when the baffle length is increased, the baffles provide increased stabilization effects. The model predicts greatest dissipation for radial modes with a hub radius at approximately half the chamber's radius.
Keywords: baffle; rocket engine; dissipation